Use of the finite elements method to calculate the strength of conical shells with notches - Kabanov, V.V.; Zheleznov, L.P. (Проблемы прочности, 1985)
The present study determines the moment stress--strain state of conical shells with notches of arbitrary size and form under complex loading. The problem is solved by the finite elements method in displacements.